Pengaruh Model Pembelajaran Think Talk Write (TTW) Berbasis Web Liveworksheets Terhadap Kemampuan Berpikir Kritis Siswa - Yuli, Riskita Candra (Peneliti.net, 2023)
This study explores how students critical thinking abilities are affected by web based liveworksheets that are based on the Think Talk Write learning model approach, which is based on online live worksheets. The purpose of this study is to ascertain how Think Talk Write (TTW) learning model, which is bades on online liveworksheets, affect critical thinking abilities. This study employs a quantitative methodology, nonequivalent control group research design, and quasi experimental study research methods. In this investigation, random sampling was chosen as the sample method. 15 multiple choice questions and 5 description questions made up the test served as the study instrumen. The findings of this study demonstrate how the aviability of liveworksheets for a web based TTW learning paradigm might influence the development of critical thinking abilities. This is demonstrated by the considerable difference in test outcames between the experimental class and the control class following the implementation of the liveworksheets based TTW learning model.